Analisis Tingkat Pendapatan, Kepercayaan dan Reputasi terhadap Minat Muzakki dalam Membayar Zakat dengan Religiusitas sebagai Variabel Moderating - Nanik Setyo Utami; Ahmad Mifdlol Muthohar; Musalim Ridlo (IQTISHODUNA, 2021)
The purpose of this research is to analyze the influence of income level, trust, and reputation toward donators’ interest to pay Zakat with religiosity as the moderating variable (case study of BAZNAS in Yogyakarta). The method of data collection is done through questionnaire shared by donators at BAZNAS in the city of Yogyakarta. This research studies 100 respondents using purposive sampling. The data obtained then are analyzed using SPSS 20 version. This analysis examines the validity, reliability, classic assumption, statistics through t statistics, f statistics, coefficient determination (R2), and moderated regression analysis (MRA).  Based of the result of t analysis, it shows that the variable of income level and reputation gives the positive influence and insignificances toward the donators’ interest in paying the Zakat. Meanwhile, the variable of trust and religiosity gives positive influence and significances toward the donators’ interest in paying the Zakat. In moderated Regression Analysis (MRA), it states that religiosity does not moderate the income level, trust and reputation toward the donators’ interests in paying Zakat.